2012
DOI: 10.1136/bjsports-2012-090979
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Olympic-style taekwondo kicks on an instrumented head-form and resultant injury measures

Abstract: The TK is of concern because it is the most common technique and cause of concussion in taekwondo. Future studies should aim to understand rotational accelerations of the head.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 21 publications
2
33
0
Order By: Relevance
“…However, the maximum kicking foot speeds reported for both back kick and the turning kick are similar to those reported by Fife et al (2012) . Furthermore, the reaction times were similar to the reaction times of elite karate practitioners (Curran and Frossard 2012).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…However, the maximum kicking foot speeds reported for both back kick and the turning kick are similar to those reported by Fife et al (2012) . Furthermore, the reaction times were similar to the reaction times of elite karate practitioners (Curran and Frossard 2012).…”
Section: Discussionsupporting
confidence: 85%
“…Although there are a number of earlier studies (Capozzo et al 1997;Curran and Frossard 2012;Fife et al 2012) that have reported kinematic and kinetic assessment of taekwondo kicks, our study present three (i.e., cut, fast, tornado kick) techniques that have not been presented in the literature before. Because we included three additional kicks that are most often used for scoring during competition, the results of this study provide a base of comparison for future studies aiming to evaluate the effects of various impairment types on taekwondo performance variables.…”
Section: Discussionmentioning
confidence: 99%
“…There were no differences between the left and right sides of the helmet. However, as the turning kick is reported to produce the highest RLA (ie, greater than 130 g),21 22 improved protection at both sides should be provided.…”
Section: Discussionmentioning
confidence: 99%
“…27 The incidence of concussion in adult taekwondo ranges from 4.6 to 50.2 per 1000 athletic exposures, potentially up to 4 times higher than that in American football. 27,28 One study of adult Olympic taekwondo kicks, measured by a simulated head target, reported that the most common kick impacts used in taekwondo had acceleration and recorded impacts equivalent to or greater than documented concussive injuries in American football. 28 Taekwondo rule changes have awarded more points for kicks aimed at the head, which may increase the risk of concussion.…”
Section: Injury Riskmentioning
confidence: 99%
“…27,28 One study of adult Olympic taekwondo kicks, measured by a simulated head target, reported that the most common kick impacts used in taekwondo had acceleration and recorded impacts equivalent to or greater than documented concussive injuries in American football. 28 Taekwondo rule changes have awarded more points for kicks aimed at the head, which may increase the risk of concussion. 27 Ineffective blocking skills may be related to risk of severe head injuries.…”
Section: Injury Riskmentioning
confidence: 99%